2015
DOI: 10.1051/0004-6361/201424663
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-steady vortices in protoplanetary disks

Abstract: Aims. We determine the size, structure, and evolution of persistent vortices in 2D and inviscid Keplerian flows. Methods. A Gaussian model of the vortices is built and compared with numerical solutions issued from non-linear hydrodynamical simulations. Test vortices are also produced using a fiducial method based on the Rossby wave instability to help explore the vortex parameters. Numerical simulations are performed using a second order finite volume method. We assume a perfect-gas law and a non-homentropic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 33 publications
(41 reference statements)
9
54
0
Order By: Relevance
“…Hence, the vortex is introduced at the beginning of the simulations and, in a few rotations, adjusts to a quasi-steady vortex structure that lasts long enough to significantly perturb the motion of the dust particles. Two dimensional vortices are, indeed, quasi-steady gaseous structures that can survive over very long time periods of up to thousands of vortex rotations around the star (Surville & Barge 2015). Their lifetimes in numerical simulations are shorter when dust is included in the A122, page 2 of 10 disk due to the gas drag, but the present simulations show that the vortices can survive long enough to significantly change the dust surface density and to imprint observable structures in the disks.…”
Section: Vortex Modelmentioning
confidence: 58%
See 2 more Smart Citations
“…Hence, the vortex is introduced at the beginning of the simulations and, in a few rotations, adjusts to a quasi-steady vortex structure that lasts long enough to significantly perturb the motion of the dust particles. Two dimensional vortices are, indeed, quasi-steady gaseous structures that can survive over very long time periods of up to thousands of vortex rotations around the star (Surville & Barge 2015). Their lifetimes in numerical simulations are shorter when dust is included in the A122, page 2 of 10 disk due to the gas drag, but the present simulations show that the vortices can survive long enough to significantly change the dust surface density and to imprint observable structures in the disks.…”
Section: Vortex Modelmentioning
confidence: 58%
“…In our problem the two conditions are satisfied except (i) when the particle size is larger than one centimeter or (ii) when located in the core of the vortex and close to its orbital radius where dust strongly accumulates. The code was previously developed to study the dynamical evolution of protoplanetary disks (Inaba et al 2005;Surville & Barge 2015). It solves the inviscid continuity and Euler equations vertically integrated over the disk thickness.…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The connection between hydrodynamic simulations was previously done by taking azimuthally averaged profile of gas obtained in hydrodynamic simulations and performing the dust coagulation calculation in a postprocessing step (Pinilla et al 2012;Carballido et al 2016). Tamfal et al (2018) included a simplified prescription for dust growth in hydrodynamic code RoSSBi (Surville & Barge 2015;Surville et al 2016), where dust is represented by a single fluid but dust size may be different in every cell and is set in a sub-grid algorithm based on the work of Birnstiel et al (2012), and demonstrated that this approach yields significantly different outcome than fixed-size treatment. Vorobyov et al (2018) implemented a similar method, with two dust populations, where dust growth is limited by barriers as proposed by Birnstiel et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this work we employ the finite volume code RoSSBi (Surville & Barge 2015;Surville & Mayer 2018), which uses the fluid approximation to treat both the gas and the dust component of the disk, solving the relevant equations in two dimensions and in cylindrical coordinates. The evolution of the dust and gas surface density (Σ d , Σ g ) is described by the inviscid Euler equations in a cylindrical coordinate system.…”
Section: Two-fluid Simulation Techniquementioning
confidence: 99%